2017
DOI: 10.1071/hc16055
|View full text |Cite
|
Sign up to set email alerts
|

New screen on the block: non-invasive prenatal testing for fetal chromosomal abnormalities

Abstract: Non-invasive prenatal testing (NIPT) is a new screen for fetal chromosomal abnormalities. It is a screening test based on technology that involves the analysis of feto-placental DNA that is present in maternal blood. This DNA is then analysed for abnormalities of specific chromosomes (eg 13, 18, 21, X, Y). NIPT has a much higher screening capability for chromosomal abnormalities than current combined first trimester screening, with ~99% sensitivity for trisomy 21 (Down syndrome) and at least a 10-fold higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…In 1997, Lo et al reported that plasma from pregnant women carrying male fetuses contained cell-free DNA (cf-DNA) derived from the Y-chromosome [1]. Then, cell-free fetal DNA (cff-DNA) was subsequently reported to be used to detect fetal Down’s syndrome and additional fetal aneuploidies in clinical practice [24]. Now, noninvasive prenatal testing (NIPT) for fetal aneuploidies by scanning cell-free fetal DNA in maternal plasma is rapidly becoming a first-tier aneuploidy screening test in clinical practice [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Lo et al reported that plasma from pregnant women carrying male fetuses contained cell-free DNA (cf-DNA) derived from the Y-chromosome [1]. Then, cell-free fetal DNA (cff-DNA) was subsequently reported to be used to detect fetal Down’s syndrome and additional fetal aneuploidies in clinical practice [24]. Now, noninvasive prenatal testing (NIPT) for fetal aneuploidies by scanning cell-free fetal DNA in maternal plasma is rapidly becoming a first-tier aneuploidy screening test in clinical practice [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of cell-free fetal DNA (cffDNA) in maternal plasma by Lo et al in 1997 has opened up new approaches for NIPT [1] . At present, NIPT has been gradually applied as a rst-tier aneuploidy screening strategy in clinical practice [2][3][4] . Previous large-scale clinical studies have revealed high accuracy of NIPT in screening on trisomy 21, 18 and 13, with sensitivity and speci city higher than 95% [5,6] , and the PPV range of trisomy 21 was 65-94%, trisomy 18 was 47-85%, and trisomy 13 was 12-62% [4,7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of cell-free fetal DNA (cffDNA) in maternal plasma by Lo et al in 1997 has opened up new approaches for NIPT [1]. At present, NIPT has been gradually applied as a rst-tier aneuploidy screening strategy in clinical practice [2][3]. Previous large-scale clinical studies have revealed high accuracy of NIPT in screening on trisomy 21, 18 and 13, with sensitivity and speci city higher than 95% [4][5].…”
Section: Introductionmentioning
confidence: 99%